Identification of E1-E4 allele combinations and ecological adaptability of soybean varieties from different geographical origins in China - Zheng, Naiwen; Guo, Yukai; Wang, Siyu; Zhang, Han; Wang, Li; Gao, Yang; Xu, Mei; Wang, Wenyan; Liu, Weiguo; Yang, Wenyu (Frontiers in Plant Science, 2023)
The duration of soybean growth and development is regulated by E1-E4 allele genes, which form the basis for ecological adaptation related to biomass accumulation, flowering and pod formation, maturation, and yield. To elucidate the effects of different combinations of E1-E4 allele genes on soybean ecological adaptation, this study conducted competitive allele-specific PCR (KASP) analysis and photoperiod gene typing on 101 main soybean cultivars from different latitudes in China. The ecological adaptation of these cultivars in Sichuan was also investigated. The results showed that within a certain range (60-95 days), soybean varieties with a genotype combination of E1/e2-ns/E3/E4 exhibited a longer growth period and demonstrated higher biomass and yield, displaying overall better performance. These varieties showed strong ecological adaptation in the Chengdu Plain region and are suitable for introduction in similar low to mid-latitude areas like the Chengdu Plain (30°N~32°N). Conversely, soybean varieties carrying a higher number of recessive alleles of E1-E4 are not suitable for introduction in this region.